ONERA-DLR bistatic SAR campaign:Planning, data acquisition, and first analysis of bistatic scattering behavior of natural and urban targets - Dubois-Fernandez, Pascale; Cantalloube, Hubert; Vaizan, Bernard; Krieger, Gerhard; Horn, Ralf; Wendler, Michael; Giroux, Vincent (IET Radar Sonar and Navigation, 2004)
Bistatic configuration is an attractive concept for spaceborne and airborne SAR missions when distributed radars are necessary as for example in the case of interferometric applications. The first reason is the important cost reduction achieved over the multiple radar elements, by having only one transmitter (expensive part) and multiple receivers. The most promising applications are single-pass interferometry with a large baseline and target or surface characterisation from bistatic scattering signature analysis. In a defence context, the improved stealth associated with the receive-only component can provide a wider operational capability. In order to explore the potentials and technical challenges associated with bistatic radar, DLR and ONERA have conducted a joint bistatic airborne radar experiment involving both their SAR systems E-SAR and RAMSES between October 2002 and February 2003. Two main geometrical configurations were flown to explore different scientific and technical objectives. In the first geometrical configuration, the quasi-monostatic mode, the two planes were flying very close to each other to acquire interferometric data in a single-pass cross-platform configuration with large interferometric baselines. The second geometrical configuration was designed to acquire images with a large bistatic angle. The two planes were flying on parallel tracks around 2 km apart, at about the same altitude, with the antennas pointing at the same area on the ground. The authors describe this research programme, including the preparation phase, the analysis of the technological challenges that had to be solved before the acquisition, the strategy adopted for bistatic image processing, the first results and a preliminary analysis of the acquired images.
DLR Import::2019-04-02